Pengaruh Brand Image, Kualitas Produk, dan Persepsi Harga terhadap Keputusan Pembelian Produk The Body Shop di Kota Surabaya - Simatupang, Sarah Regina; Pudjoprastyono, Hery; Mandasari, Virginia (Universitas Batanghari, 2024)
The Body Shop is a beauty brand known for its commitment to environmental responsibility. However, between 2019 and 2023, The Body Shop experienced a decline due to various factors. This research aims to examine whether Brand Image, Product Quality, and Price Perception influence consumers' purchasing decisions for The Body Shop products in Surabaya. The population in this study consists of residents of Surabaya who have purchased and used The Body Shop products. This research employs a quantitative method with 115 respondents selected through purposive sampling, a sampling technique based on specific criteria. The analysis applied in this study is Partial Least Square (PLS). The research results indicate that Brand Image, Product Quality, and Price Perception have a positive and significant impact on purchasing decisions for The Body Shop products in Surabaya..